Can digital transformation improve the transparency and accountability of Indonesian public governance? - M. Irwan Tahir; Ani Martini; Anak Agung Ngurah Gunawan; Yogi Makbul; Nirma Yossa; Wisber Wiryanto; Moch Fahrudin; Rahmat Ilya (International Journal of Data and Network Science)
The development of information technology is currently growing rapidly, affecting all aspects of life. There are various benefits obtained from advances in information technology, one of which is the ease of communicating and accessing information. This transformation is an opportunity to increase accessibility in various sectors, such as government, health, education, social, economic and other sectors. This research aims to analyze the relationship between digital transformation and public accountability, digital transformation with public transparency and transparency with public accountability. The research uses quantitative methods to test the relationship between variables. The respondents of this research were 478 government public service office employees who were determined using a simple random sampling method. Research data analysis uses structural equation modelling (SEM) partial least squares (PLS) with research data analysis tools using SmartPLS 3.0 software. Based on the results of data analysis, it is concluded that digital transformation had a positive and significant relationship to public accountability, digital transformation had a positive and significant relationship to public transparency and transparency had a positive and significant relationship to public accountability. The process of digital transformation in public administration greatly influences how public services are delivered and how government functions. Leveraging digital technology is an opportunity to increase accessibility in various fields such as government, health, education, economics, social and politics. Public administration can increase transparency, efficiency, public participation and data-based decision-making. Organizations pursuing digital transformation must be flexible, innovative and able to adapt quickly. Several important benefits of transparency include preventing corruption, making it easier to identify weaknesses and strengths of a policy, and increasing accountability in the delivery of public services by government agencies. In addition, a transparent attitude will increase trust in government institutions to decide on certain policies, as well as being able to encourage a conducive investment climate and increase business certainty.